Field Reaction Experiments of Carbonate Minerals in Spring Waters: Natural Analogue of Geologic CO2 Storage - Masao Sorai; Munetake Sasaki; Takahiro Kuribayashi (Geofluids)
To diminish the uncertainty of the mineral trapping rate during geologic CO2 storage, the growth rate of carbonate minerals was measured in CO2-containing spring waters, which can be regarded as a natural analogue of geologic CO2 storage. The authors’ approach, using nanoscale analysis of seed crystal surfaces after immersion into spring waters, enables rapid and accurate measurement of mineral reaction rates. The results show that calcite growth rates in spring waters were lower by 1–3 orders than the values given in a database of laboratory experiment results. We verified the traditional paradigm that Mg2+ controls carbonate reaction kinetics. An increase of the Mg/Ca ratio to around 5 by adding Mg2+ to spring waters markedly reduced the calcite growth rate. However, even if effects of Mg2+ and flow rate are considered, we were unable to explain satisfactorily the difference of the calcite growth rates between those of spring waters and laboratory experiments. Therefore, other factors might also be related to the slow growth rate in nature. The present results, including the fact such that neither dolomite nor magnesite was formed even at the high Mg/Ca ratio, are expected to provide an important constraint to overestimation of the mineral trapping rate.